RANCANG BANGUN MESIN PENGERING SEPATU RAMAH LINGKUNGAN DENGAN SISTEM HEATER - Jaelani Jaelani; Sudarmono Sudarmono; Muhd Hafizal Fitri (JOURNAL SAINS STUDENT RESEARCH, 2026)
. Environmentally friendly shoe dryer and analyze the effect of the heater heating system on shoe drying rate. The background to this research arose from the need for a faster and more hygienic shoe drying method than drying in the sun, which is often time-consuming, impractical, and has the potential to cause odors or mold. Furthermore, this design incorporates "environmentally friendly" aspects through energy efficiency and optimal resource utilization. The research method will involve three main stages: (1) Literature Review and Design of the dryer, including selecting the heater type (ceramic heater or other heating element) and efficient materials. (2) Fabrication or creation of a dryer prototype. (3) Performance Testing, where the device will be tested using varying heater temperatures to measure the drying rate (g/hour) and the time required for shoes to dry completely. Test data will be analyzed to determine optimal operating conditions in terms of speed and energy efficiency. The expected outcome of this research is the creation of a shoe drying prototype that can reduce drying time by 60/120 minutes compared to conventional methods, while also being more energy efficient. This design is expected to be a practical, hygienic, and environmentally friendly solution for users.